'It's like she is a hologram stuck behind my eyes': Cybernetics and gendered spectrality in William Gibson's Burning Chrome. Issue 2 (1st October 2017) - Girard, Gaïd
Rereading the short stories contained in the Burning Chrome collection published in 1986 is a rewarding experience. With two exceptions, all the stories predate the publication of Neuromancer (1984), the novel that made William Gibson world famous and launched the cyberpunk genre. Indeed, the concept of cyberspace is present in the title short story of the collection and so is the idea of a matrix, which hackers try to break into and 'burn'. Nearly all the stories resort to male first-person narrators. The proximity and subjectivity thus created between reader and narrator crudely highlights the way in which female characters are pushed to the periphery of an already disembodied and spectralized world. Through a close look at 'Burning Chrome', 'The New Rose Hotel' and 'Winter Market', this article aims to show how corporate global capitalism as represented by Gibson paradoxically reinforces the invisibility of women by using state-of-the art technology to turn them into seductive holograms, disembodied voices and spectral presences. The question is: can the Gibson women fight back against this centrifugal move towards non-existence and how do they go about it?